(untitled) (Collection of scientific works «Modern structures of metal and wood», 2025)
The paper investigates the stability of steel vertical cylindrical tanks under wind load. Cylindrical tanks as thin-walled structures are vulnerable to compressive loads. The analysis of the behaviour of tanks under wind pressure, which can cause a loss of stability, is important. Analysis of publications. An overview of research works on the behaviour of thin-walled shells and tanks under external pressure is presented. It has been found that for the class of problems under consideration, critical loads do not always coincide with the limit loads. The difference in results depends on the nature of the load and the accuracy of determining the initial state of the shells. The ranges of relevance of the simplified calculation models were established. However, the geometric parameters of the studied shells do not correspond to the geometric parameters of the tanks. An analysis of the design standards methodology showed its shortcomings. This is an insufficient consideration of the geometric parameters of the tanks, the conditions of shell anchoring and the actual nature of the wind load distribution. This failure to take into account can lead to significant errors in the determination of critical loads. This can lead to a risk to the tanks safe operation. The aim of the study is to determine the effective parameters of FEM-models of cylindrical tanks for analysing their behaviour under wind load, taking into account the actual nature of its distribution. Main material and results. The calculations were carried out in the LIRA software package of the computer-aided design system. Different variants of boundary conditions were considered: free support and rigid clamping of the shell ends. The finite element mesh was gradually thickened to ensure convergence of the results. Refinement was stopped if the difference between two consecutive solutions did not exceed 5%. Conclusions. It is shown that the solution of the problem stabilises at some partitioning of the nynx shell into finite elements. For several adjacent partitions, the solution of the problem becomes constant. Such discretization was taken as the range of effective discretization of the shell into FEs. Recommendations for determining the effective parameters of FEM models of the tanks under the action of external pressure are given. It was found that the deviation of the numerical values of the critical uniform pressure for the analysed shells from the corresponding analytical values was 5-9%. This is a sufficient accuracy of the results obtained. The calculated numerical critical value of the wind pressure exceeds the critical uniform pressure for the considered shells. This excess is 19-40%.